2022
DOI: 10.3390/e24121761
|View full text |Cite
|
Sign up to set email alerts
|

How, Why and When Tsallis Statistical Mechanics Provides Precise Descriptions of Natural Phenomena

Abstract: The limit of validity of ordinary statistical mechanics and the pertinence of Tsallis statistics beyond it is explained considering the most probable evolution of complex systems processes. To this purpose we employ a dissipative Landau–Ginzburg kinetic equation that becomes a generic one-dimensional nonlinear iteration map for discrete time. We focus on the Renormalization Group (RG) fixed-point maps for the three routes to chaos. We show that all fixed-point maps and their trajectories have analytic closed-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Recently [ 25 ], we have demonstrated that the trajectories of all RG fixed-point maps for the three known routes to chaos (intermittency, period doubling, and quasi-periodicity [ 24 ]) can be couched in the statistical–mechanical language of the (discrete time) Landau–Ginzburg (LG) equation. Additionally, the associated Lyapunov function [ 40 ] is precisely the expression for the Tsallis entropy [ 25 ]. Equation ( 10 ) is a particular case of the LG equation used to describe the most probable evolution of processes in statistical–mechanical systems.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently [ 25 ], we have demonstrated that the trajectories of all RG fixed-point maps for the three known routes to chaos (intermittency, period doubling, and quasi-periodicity [ 24 ]) can be couched in the statistical–mechanical language of the (discrete time) Landau–Ginzburg (LG) equation. Additionally, the associated Lyapunov function [ 40 ] is precisely the expression for the Tsallis entropy [ 25 ]. Equation ( 10 ) is a particular case of the LG equation used to describe the most probable evolution of processes in statistical–mechanical systems.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This driving force is the (functional) derivative of the Lyapunov function. This function represents a generalized thermodynamic potential and evolves monotonically as t , or N , increases along the solution of the LG equation [ 25 ]. In the case of Equations ( 10 ) and ( 17 ), it is given by The Tsallis entropy above corresponds to a uniformly distributed set of events.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations